Preparation method of cellulose-based ZIFs / GO composite material with sandwich structure
By compositeing graphene oxide (GO) with cellulose nanofibers (CNF) and ZIFs materials, a sandwich structure cellulose-based ZIFs/GO composite material is formed, which solves the problem of poor dispersion of ZIFs materials in aqueous solution and improves its adsorption performance and reuse rate.
Patent Information
- Application Number
- CN202411609624.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-28
AI Technical Summary
ZIFs materials have poor dispersion in aqueous solution, which affects their adsorption properties.
Using the preparation method of sandwich structure cellulose-based ZIFs/GO composite material, graphene oxide (GO) is composited with cellulose nanofibers (CNF) and ZIFs materials to form a composite material with high adsorption performance and reuse rate.
The dispersion and adsorption properties of ZIFs materials in water are improved, the adsorption capacity of ZIFs materials to organic pollutants in water is enhanced, and the cost of use is reduced.
Smart Images

Figure CN119524813A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorption material preparation, and in particular to a method for preparing a sandwich-structured cellulose-based ZIFs / GO composite material. Background Art
[0002] With the rapid development of industry, industrial wastewater will inevitably increase; in order to reduce the impact of industrial wastewater on the environment and people's health, the treatment of industrial wastewater is particularly important. At present, the main methods for treating industrial wastewater are biodegradation, advanced oxidation, membrane filtration, and adsorption. Among them, adsorption is considered to be one of the most promising methods for treating low-content and complex organic pollutants due to its high removal efficiency, environmental friendliness, easy preparation, and reusability; adsorption is achieved by adsorbing the target molecules or ions from the liquid to the internal and external surfaces through adsorbents. In this process, the adsorption material is the key factor affecting the adsorption process, and the physical and chemical structure of the adsorption material directly affects the adsorption performance of the separation process.
[0003] Zeolitic Imidazolate Frameworks (ZIFs) are a subclass of metal-organic framework materials and are generally composed of Zn 2+ or Co 2+ The ions and the imidazole groups of the organic ligands are bridged by N atoms to form a three-dimensional porous framework structure. Different imidazole organic ligands can be used to form ZIFs materials with different topological structures. ZIFs materials not only have the structural characteristics of zeolites, but also have pore sizes larger than molecular sieves with the same structure. Therefore, ZIFs materials can replace zeolites as a new type of porous material with excellent performance and good prospects. In addition, compared with other types of metal-organic framework materials, ZIFs materials show superior thermal and chemical stability and can remain stable in boiling alkaline aqueous solutions and organic solvents; the advantages of ZIFs materials such as porous structure, high porosity, adjustable pore size and strong physical and chemical stability make them high-performance separation materials used in the separation of organic pollutants in water.
[0004] Although ZIFs materials have great potential in adsorption and separation applications, hydrophobic ZIFs powders have poor dispersibility and are easy to agglomerate in aqueous solutions, which is not conducive to comprehensive contact with the adsorbate, thus affecting the adsorption performance. In order to further improve the shortcomings of ZIFs materials that limit their application, they are usually hybridized with nanomaterials, polymer materials or two-dimensional materials.
[0005] Cellulose nanofibrils (CNFs) are a kind of nanocellulose material with wide sources, low cost, good biocompatibility, special network structure, rich hydroxyl and carboxyl functional groups, strong chelating ability for heavy metals, and can be used as carriers to fix functionalized nanomaterials to improve the physical and chemical properties and adsorption properties of composite materials. The composite of CNF and ZIFs nanomaterials is of great significance for the adsorption and separation of organic pollutants in water, which can not only improve the dispersibility of ZIFs in water, but also improve the adsorption properties of functional composite nanomaterials.
[0006] Graphene oxide (GO) nanosheets are considered to be "soft" two-dimensional macromolecules with multiple hydrophobic aromatic regions and hydrophilic oxygen-containing groups; the unique amphiphilicity of GO enhances the solubility of insoluble nanoparticles; among them, the abundant oxygen-containing groups on the surface of GO are conducive to its binding with non-coordinating organic monomers and metal ions on ZIFs, therefore, the introduction of graphene oxide is expected to solve the problem of poor dispersibility of ZIFs; in addition, the insertion of ZIFs / CNF composites between GO sheets can reduce the restacking between nanosheets and improve the overall stability and physicochemical properties of the composites in aqueous environments. Summary of the invention
[0007] In view of this, the present invention provides a method for preparing a sandwich structure cellulose-based ZIFs / GO composite material. The method uses graphene oxide having multiple hydroxyl and carboxyl groups as a carrier, firstly complexes metal ions Co 2+ , and then mixed with CNF dispersion, and mixed with ligand solution by in situ growth method to prepare ZIFs / CNF / GO composite material; the ZIFs / CNF / GO composite material has the advantages of strong adsorption capacity and high reuse rate.
[0008] The technical solution of the present invention is as follows: A method for preparing a sandwich structured cellulose-based ZIFs / GO composite material, the process is as follows: (1) Dissolve GO in deionized water and sonicate for 15-20 min to obtain a GO / water dispersion with a weight-to-volume ratio of GO to deionized water (mg / mL) of 5-6:1; Co(NO3)2•6H2O was dissolved in deionized water and then mixed with GO / water dispersion and stirred for 2-3h to obtain Co 2+ / GO mixed solution; (2) Take cellulose nanofiber (CNF) solution and add Co 2+ / GO mixture, stirred for 3-4h to obtain CO 2+ / GO / CNF mixed solution; (3) Dissolve 2-methylimidazole in methanol and then react with CO2+ / GO / CNF mixed solution was mixed and stirred for 12-14 hours. After filtering, a blue-purple solid was obtained. After washing with methanol and deionized water for multiple times, the solid was centrifuged and dried to obtain a ZIF-67 / CNF / GO composite material.
[0009] Preferably, in step (1), the weight-to-volume ratio (mg / mL) of GO to deionized water is 5:1.
[0010] Preferably, in step (1), the mass ratio of GO to Co(NO3)2•6H2O is 1:6-15.
[0011] Preferably, in step (2), the concentration of the CNF solution is 6 wt %.
[0012] Compared with the prior art, the beneficial effects of the present invention are: 1. The ZIF-67 / CNF / GO composite material obtained by the preparation method provided by the present invention has high adsorption and separation performance, and can efficiently adsorb organic pollutants in water; it also has a high reuse rate and reduces the cost of use; in addition, the ZIF-67 / CNF / GO composite material has efficient and rapid adsorption performance.
[0013] 2. In the present invention, two-dimensional graphene oxide (GO) with multiple hydroxyl and carboxyl groups is used as a carrier to load the chain ZIFs / CNF material, so that the obtained ZIF-67 / CNF / GO composite material presents a sandwich structure; and the introduction of GO can provide ZIFs with abundant oxygen-containing groups and contact nodes to facilitate the bonding between the two, which helps the chain ZIFs / CNF composite material to grow on the surface or interlayer of GO to form a new sandwich channel structure.
[0014] 3. The sandwich-structured cellulose-based ZIFs / GO composite material prepared by the method of the present invention can combine the respective advantages of the three to overcome the defects of ZIFs themselves and improve its adsorption performance for antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0016] Figure 1Surface scanning electron micrographs of the composite materials prepared in Comparative Example 1 and Examples 1-4, in which a is ZIF-67 / CNF, b is ZIF-67 / CNF / GO-6, c is ZIF-67 / CNF / GO-9, d is ZIF-67 / CNF / GO-912, and e is ZIF-67 / CNF / GO-15.
[0017] Figure 2 The XRD diagrams of the composite materials prepared in Comparative Example 1 and Examples 1-4 are shown.
[0018] Figure 3 FTIR images of the composite materials prepared in Comparative Example 1 and Examples 1-4 DETAILED DESCRIPTION In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] Example 1 Combination Figure 1 The present invention provides a method for preparing a sandwich structured cellulose-based ZIF-67 / GO composite material, the process being as follows: (1) Dissolve 100 mg GO in 20 mL deionized water and sonicate for 15 min to obtain GO / water dispersion; 120 mg of Co(NO3)2•6H2O was dissolved in 10 mL of deionized water and then mixed with GO / water dispersion and stirred for 2 h to obtain Co 2+ / GO mixed solution; wherein the mass ratio of GO to Co(NO3)2•6H2O is 1:6; (2) Take 2 g of 6 wt% carbon nanofiber (CNF) solution and add Co 2+ / GO mixed solution was stirred for 3 h to obtain CO 2+ / GO / CNF mixed solution; (3) Dissolve 1.2 g of 2-methylimidazole in 50 mL of methanol and then react with CO 2+ / GO / CNF mixed solution was mixed and stirred for 12 h, and then filtered to obtain a blue-purple solid; The resultant product was washed three times with methanol and deionized water respectively, centrifuged and dried to obtain a ZIF-67 / CNF / GO-6 composite material.
[0020] Example 2 A method for preparing a sandwich structured cellulose-based ZIF-67 / GO composite material, the process is as follows: (1) Dissolve 100 mg GO in 20 mL deionized water and sonicate for 15 min to obtain GO / water dispersion; 180 mg of Co(NO3)2•6H2O was dissolved in 10 mL of deionized water and then mixed with GO / water dispersion and stirred for 2 h to obtain Co 2+ / GO mixed solution; wherein the mass ratio of GO to Co(NO3)2•6H2O is 1:9; (2) Take 2 g of 6 wt% carbon nanofiber (CNF) solution and add Co 2+ / GO mixed solution was stirred for 3 h to obtain CO 2+ / GO / CNF mixed solution; (3) Dissolve 1.8 g of 2-methylimidazole in 50 mL of methanol and then react with CO 2+ / GO / CNF mixed solution was mixed and stirred for 12 h, and then filtered to obtain a blue-purple solid; The resultant product was washed three times with methanol and deionized water, respectively, centrifuged and dried to obtain a ZIF-67 / CNF / GO-9 composite material.
[0021] Example 3 A method for preparing a sandwich structured cellulose-based ZIF-67 / GO composite material, the process is as follows: (1) Dissolve 100 mg GO in 20 mL deionized water and sonicate for 15 min to obtain GO / water dispersion; 240 mg of Co(NO3)2•6H2O was dissolved in 10 mL of deionized water and then mixed with GO / water dispersion and stirred for 2 h to obtain Co 2+ / GO mixed solution; wherein the mass ratio of GO to Co(NO3)2•6H2O is 1:12; (2) Take 2 g of 6 wt% carbon nanofiber (CNF) solution and add Co 2+ / GO mixed solution was stirred for 3 h to obtain CO 2+ / GO / CNF mixed solution A; (3) Dissolve 2.4 g of 2-methylimidazole in 50 mL of methanol and then react with CO 2+ / GO / CNF mixed solution was mixed and stirred for 12 h, and then filtered to obtain a blue-purple solid; The resultant product was washed three times with methanol and deionized water respectively, centrifuged and dried to obtain a ZIF-67 / CNF / GO-12 composite material.
[0022] Example 4 A method for preparing a sandwich structured cellulose-based ZIF-67 / GO composite material, the process is as follows: (1) Dissolve 100 mg GO in 20 mL deionized water and sonicate for 15 min to obtain GO / water dispersion; 300 mg of Co(NO3)2•6H2O was dissolved in 10 mL of deionized water and then mixed with the GO / water dispersion and stirred for 2 h to obtain Co 2+ / GO mixed solution; wherein the mass ratio of GO to Co(NO3)2•6H2O is 1:15; (2) Take 2 g of 6 wt% carbon nanofiber (CNF) solution and add Co 2+ / GO mixed solution was stirred for 3 h to obtain CO 2+ / GO / CNF mixed solution; (3) Dissolve 3 g of 2-methylimidazole in 50 mL of methanol and then react with CO 2+ / GO / CNF mixed solution was mixed and stirred for 12 h, and then filtered to obtain a blue-purple solid; The resultant product was washed three times with methanol and deionized water, centrifuged and dried to obtain a ZIF-67 / CNF / GO-15 composite material.
[0023] Comparative Example 1 Take 240 mg of Co(NO3)2•6H2O and dissolve it in 10 mL of deionized water. Then add 2 g of 6 wt% CNF solution, mix and stir for 3 h, then add 48 mg / mL 2-methylimidazole solution, mix and stir for 12 h, filter and collect the precipitate; the precipitate is washed with methanol and deionized water 4 times, filtered and dried to obtain ZIF-67 / CNF composite material.
[0024] Detection: The ZIF-67 / CNF composite material with a chain structure prepared in Comparative Example 1, the ZIF-67 / CNF / GO-6 composite material with a sandwich structure prepared in Example 1, the ZIF-67 / CNF / GO-9 composite material with a sandwich structure prepared in Example 2, the ZIF-67 / CNF / GO-12 composite material with a sandwich structure prepared in Example 3, and the ZIF-67 / CNF / GO-15 composite material with a sandwich structure prepared in Example 4 were observed by surface scanning electron microscopy, and the results are shown in FIG. Figure 2 ; like Figure 2 As shown, in the ZIF-67 / CNF composite material prepared in Comparative Example 1, ZIF-67 can form a good chain structure with CNF, wherein the size of the ZIF-67 nanoparticles is about 50 nm; In the ZIF-67 / CNF / GO-6 composite material prepared in Example 1, the ZIF-67 / CNF / GO-9 composite material prepared in Example 2, the ZIF-67 / CNF / GO-12 composite material prepared in Example 3, and the ZIF-67 / CNF / GO-15 composite material prepared in Example 4, the addition of GO makes the rich oxygen-containing groups on its surface conducive to its binding with the non-coordinating organic monomers and metal ions on ZIFs, and the chain ZIF-67 / CNF and GO are tightly combined to form a unique sandwich structure; with the increase of cobalt salt content, the particles are arranged more tightly, and after reaching a certain degree, they are arranged loosely. When the ratio of cobalt salt to GO is 1:12 (Example 3), the ZIF-67 nanoparticles are tightly arranged on the GO sheet without obvious defects, which will help to improve the adsorption performance.
[0025] Adsorption test: 10 mg of ZIF-67 / CNF composite material, ZIF-67 / CNF / GO-6 composite material, ZIF-67 / CNF / GO-9 composite material, ZIF-67 / CNF / GO-12 composite material and ZIF-67 / CNF / GO-15 composite material were added into 10 mL of 50 mg / L Congo red solution, and the color change was observed after adsorption for 3 h, and the absorbance was measured and the adsorption amount was calculated. The adsorption amount was calculated according to the following formula: formula:
[0026] Where, q is the adsorption amount, unit is mg / g; C0 is the initial concentration of Congo red solution before adsorption, in mg / L; C t is the final concentration after adsorption of Congo red solution, in mg / L; V is the volume of the Congo red solution consumed, in mL; M is the mass of the adsorbent, in mg.
[0027] The above formula was used to calculate the adsorption capacity of the composite material. The results are shown in Table 1, as follows: Table 1 Adsorption and separation performance of ZIF-67 / CNF / GO for Congo red dye aqueous solution
[0028] Table 1 shows the adsorption amount of ZIF-67 / CNF composites and ZIF-67 / CNF / GO-6 composites, ZIF-67 / CNF / GO-9 composites, ZIF-67 / CNF / GO-12 composites and ZIF-67 / CNF / GO-15 composites on Congo red solution with a concentration of 50 mg / L for 3 h; Combined with Table 1, it can be seen that with the increase of cobalt salt content, the adsorption of Congo red by ZIF-67 / CNF / GO composite material shows a trend of first increasing and then decreasing. When the ratio of GO to cobalt salt is 1:12, the maximum adsorption amount can reach 62.8 mg·g -1 , showing excellent adsorption and separation performance, which is mainly attributed to the addition of flexible GO reducing the defects between the chain ZIF-67 / CNF particles, increasing the dispersibility of the composite material in water and thus improving its adsorption performance.
[0029] In the preparation method of the present invention, the ZIFs material is compounded with cellulose nanofibers (CNF) to form a chain composite material, which can then be compounded with a two-dimensional network of graphene oxide (GO) to form a sandwich ZIFs / GO / CNF composite material. CNF helps the combination between ZIFs and GO and enhances the specific surface area, improves its dispersibility in water, and improves the adsorption performance.
[0030] Example 5 A method for preparing a sandwich structured cellulose-based ZIF-67 / GO composite material, the process is as follows: (1) Dissolve 100 mg GO in 20 mL deionized water and sonicate for 17 min to obtain GO / water dispersion; 240 mg of Co(NO3)2•6H2O was dissolved in 10 mL of deionized water and then mixed with the GO / water dispersion and stirred for 2.5 h to obtain Co 2+ / GO mixed solution; wherein the mass ratio of GO to Co(NO3)2•6H2O is 1:12; (2) Take 2 g of 6 wt% carbon nanofiber (CNF) solution and add Co 2+ / GO mixed solution was stirred for 3.5h to obtain CO 2+ / GO / CNF mixed solution; (3) Dissolve 2.4 g of 2-methylimidazole in 50 mL of methanol and then react with CO 2+ / GO / CNF mixed solution was mixed and stirred for 13 h, and then filtered to obtain a blue-purple solid; The resultant product was washed four times with methanol and deionized water, respectively, centrifuged and dried to obtain a ZIF-67 / CNF / GO-12 composite material.
[0031] Example 6 A method for preparing a sandwich structured cellulose-based ZIF-67 / GO composite material, the process is as follows: (1) Dissolve 100 mg GO in 20 mL deionized water and sonicate for 20 min to obtain GO / water dispersion; 240 mg of Co(NO3)2•6H2O was dissolved in 10 mL of deionized water and then mixed with GO / water dispersion and stirred for 3 h to obtain Co 2+ / GO mixed solution; wherein the mass ratio of GO to Co(NO3)2•6H2O is 1:12; (2) Take 2 g of 6 wt% carbon nanofiber (CNF) solution and add Co 2+ / GO mixture was stirred for 4 h to obtain CO 2+ / GO / CNF mixed solution; (3) Dissolve 2.4 g of 2-methylimidazole in 50 mL of methanol and then react with CO 2+ / GO / CNF mixed solution was mixed and stirred for 14 h, and then filtered to obtain a blue-purple solid; The resultant product was washed three times with methanol and deionized water respectively, centrifuged and dried to obtain a ZIF-67 / CNF / GO-12 composite material.
[0032] Although the present invention has been described in detail by reference to the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be subject to the scope of protection of the claims.
Claims
1. A method for preparing a sandwich structure cellulose-based ZIFs / GO composite material, characterized in that: The process is as follows: (1) Dissolve GO in deionized water and sonicate for 15-20 min to obtain a GO / water dispersion with a weight-to-volume ratio of GO to deionized water (mg / mL) of 5-6:1; Co(NO3)2•6H2O was dissolved in deionized water and then mixed with GO / water dispersion and stirred for 2-3h to obtain Co 2+ / GO mixed solution; (2) Take cellulose nanofiber (CNF) solution and add Co 2+ / GO mixture, stirred for 3-4h to obtain CO 2+ / GO / CNF mixed solution; (3) Dissolve 2-methylimidazole in methanol and then react with CO 2+ / GO / CNF mixed solution was mixed and stirred for 12-14 hours. After filtering, a blue-purple solid was obtained. After washing with methanol and deionized water for multiple times, the solid was centrifuged and dried to obtain a ZIF-67 / CNF / GO composite material.
2. The method for preparing the sandwich structure cellulose-based ZIFs / GO composite material according to claim 1, characterized in that: In step (1), the weight volume ratio (mg / mL) of GO to deionized water was 5:
1.
3. The method for preparing the sandwich structure cellulose-based ZIFs / GO composite material according to claim 1, characterized in that: In step (1), the mass ratio of GO to Co(NO3)2•6H2O is 1:6-15.
4. The method for preparing the sandwich structure cellulose-based ZIFs / GO composite material according to claim 1, characterized in that: In step (2), the concentration of the carbon nanofiber solution is 6 wt %.